Investigating knowledge, attitudes, and practices regarding vaccinations of community pharmacists in Italy - Giorgia Della Polla; Francesco Napolitano; Concetta Paola Pelullo; Caterina De Simone; Chiara Lambiase; Italo Francesco Angelillo (Taylor & Francis Group, 2020)
The purposes of this cross-sectional study were to determine the level of knowledge, attitudes, and behaviors related to vaccinations among community pharmacists in Italy and to understand the characteristics associated with the different outcomes of interest. The data were collected between September 2018 and April 2019 using semi-structured telephone interviews among a nationally representative sample of community pharmacists. Out of 550 pharmacists who were contacted, a total of 389 responded yielding a response rate of 70.7%. Only 23.9% indicated correctly all ten mandatory vaccinations for newborn. Participants with a lower number of years since degree, employee compared to owners, those who often/always collected information about public's immunization, and who have received information from educational activities were more likely to know all ten mandatory vaccinations for newborn. Almost all (91.7%) believed that they could play a prominent role in the educational interventions on vaccinations and 75.3% that they should be more engaged in these interventions. Only 23.7% had recommended HPV vaccine to 11-12 years-old adolescents. Pharmacists who have obtained information from educational activities, who knew all ten mandatory vaccinations for newborn, and who believed that they should be more engaged in vaccination interventions were more likely to recommend the vaccine. The HPV vaccine was less likely recommended by those who have obtained information from scientific journals, mass-media and internet, and educational activities compared to those who have not received any information, who worked a higher number of hours per week, who often/always collected data on immunization, and employee pharmacists compared to owners. The findings may be useful to design interventions that can overcome the knowledge gaps of community pharmacists and to improve vaccine recommendations.